Incidence and risk factors of postoperative nausea and vomiting following laparoscopic sleeve gastrectomy and its relationship with Helicobacter pylori: A propensity score matching analysis - Song, Yali; Zhu, Jie; Dong, Zhiyong; Wang, Cunchuan; Xiao, Jia; Yang, Wah (Frontiers in endocrinology (Lausanne), 2023)
Postoperative nausea and vomiting (PONV) are common after laparoscopic sleeve gastrectomy (LSG), affecting patient satisfaction and postoperative recovery. The purpose of this study was to investigate the incidence and severity of PONV after LSG and the relationship between Helicobacter pylori (HP) and PONV. Patients undergoing LSG in our center from June 1, 2018, to May 31, 2022, were divided into HP-positive and HP-negative groups for retrospective analysis. The independent risk factors of PONV were determined by univariate and binary logistic regression analysis using a 1:1 propensity score matching (PSM) method. A total of 656 patients was enrolled, and 193 pairs of HP-positive and negative groups were matched after PSM. Both groups of patients had similar clinical features and surgical procedures. PONV occurred in 232 patients (60.1%) after LSG, and the incidence of PONV in HP-positive patients was 61.10%. The incidence and severity of PONV were statistically similar in both groups (P=0.815). Multivariate analysis showed that the female sex (OR=1.644, P=0.042), postoperative pain (OR=2.203, P=0.001) and use of postoperative opioid (OR=2.229, P=0.000) were independent risk factors for PONV after LSG, whereas T2DM (OR=0.510, P=0.009) and OSAS (OR=0.545, P=0.008) independently reduced the incidence rate of PONV. There was no difference either in smoking (P=0.255) or alcohol drinking (P=0.801). HP infection did not affect PONV (P=0.678). The incidence of PONV following LSG was relatively high. Female sex, postoperative pain and use of postoperative opioid predicted a higher incidence of PONV. Patients with T2DM and OSAS were less likely to have PONV. There was no clear association between HP infection and PONV after LSG.